2016
DOI: 10.3390/insects7040069
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Impacts of Non-Native Bee Species around the World

Abstract: Though they are relatively understudied, non-native bees are ubiquitous and have enormous potential economic and environmental impacts. These impacts may be positive or negative, and are often unquantified. In this manuscript, I review literature on the known distribution and environmental and economic impacts of 80 species of introduced bees. The potential negative impacts of non-native bees include competition with native bees for nesting sites or floral resources, pollination of invasive weeds, co-invasion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
182
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(188 citation statements)
references
References 110 publications
4
182
0
2
Order By: Relevance
“…The ecological effects of these introductions range from harmful to positive, depending upon the species, the context in which it was introduced, and (in particular) the local density of the pollinator (Russo 2016). The most abundant and impactful of these introductions has been the western honey bee (Apis mellifera), managed colonies of which are used to support agricultural pollination in parts of the world far outside its native range.…”
Section: The Introduction Of Non-native Pollinatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ecological effects of these introductions range from harmful to positive, depending upon the species, the context in which it was introduced, and (in particular) the local density of the pollinator (Russo 2016). The most abundant and impactful of these introductions has been the western honey bee (Apis mellifera), managed colonies of which are used to support agricultural pollination in parts of the world far outside its native range.…”
Section: The Introduction Of Non-native Pollinatorsmentioning
confidence: 99%
“…The diversity of pollinating insects has been artificially increased in some parts of the world by the introduction of non-native species, particularly bees (Goulson 2003, Russo 2016, either purposefully, to enhance crop pollination, or accidentally. In some oceanic islands introduced species can outnumber native pollinators; for example a recently published checklist of the bees of the Azores showed that of 19 species recorded (including managed hives of honey bees) only 4 were likely to be native (Weissmann et al 2017).…”
Section: The Introduction Of Non-native Pollinatorsmentioning
confidence: 99%
“…In addition, M. sculpturalis is now present in Austria, Italy, Germany, and Switzerland and is therefore well established in mainland Europe. Several bee species have been introduced, accidentally or deliberately, outside their native range due to human activities, mainly in North and South America and in Oceania (Goulson, 2003;Russo, 2016). In the northeastern USA, for example, Bartomeus et al (2013) identified 20 bee species not native to the USA.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with North and South America, where many introduced bees have been detected, bee introductions have been rare in European countries. To our knowledge (Goulson, ; Russo, ), M. sculpturalis is the first introduced bee species in Europe, where it has been detected for the first time in 2008. The observation occurred in Allauch near Marseille, France (Vereecken & Barbier, ).…”
Section: Introductionmentioning
confidence: 99%
“…Insects are a highly species‐rich part of terrestrial ecosystems, and their positive contributions to a wide range of ecosystem services have been highlighted (Losey & Vaughan, ; Kremen & Chaplin‐Kramer, ; Nichols et al ., ). About 3000 non‐native insect species have been deliberately introduced into many countries to improve three ecosystem services: biological control of pests or weeds (Hajek et al ., ), pollination (Russo, ), or decomposition (Hanski & Cambefort, ). The vast majority of deliberate releases of non‐native insects targeted at improving ecosystem services have been for biological control of pests or weeds (Winston et al ., ; Cock et al ., ).…”
Section: Introductionmentioning
confidence: 99%